(untitled) (Alternautas, 2022)
During the last decade, Latin America has been coping with a new scenario characterized by a reborn of fiscal adjustment discourses. By 2020, the COVID-19 pandemic has deepened this policy orientation that seems to stand as central to the response to the economic crisis.This paper argued that fiscal adjustments catalyzed by the COVID-19 pandemic have highlighted gender gaps, making women poorer in terms of incomes and time. Expenditure cuts triggered by constraints in fiscal revenues have a disproportionate effect on women and children. Women are more dependent on social policies because they are over-represented in poverty rates, informal work, and lower-income sectors. Likewise, women are employed in sectors that have been severely affected by the health and economic crisis.